Constitutional legitimation "ad processum" of the indian (Revista do Tribunal Regional Federal da 3ª Região, 2011)
The constitutional legitimation of the indians to the lawsuit is analyzed from the 1988 Federal Constitution and the possibility of going into Court in proper name against the Tutor State to the defense of their own rights and interests. The analysis becomes part of the right to the access to Justice and to Court guardianship effectiveness, regarding the indian natives’ “unimportance” and“invisibility” and the necessity of interpreting the national legal system in agreement with the enlargement of the indigenous people active legality in the level of the Inter-American Court of Human Rights.
Keywords: access; effectiveness; jurisdiction; indians; lawsuit; legitimation; Inter-American Court of Human Rights